2020
DOI: 10.1021/acs.jpca.0c02575
|View full text |Cite
|
Sign up to set email alerts
|

Positron Scattering from Pyridine and Pyrimidine

Abstract: Positron impact scattering cross-sections for pyridine and pyrimidine are reported here. Spherical complex optical potential formalism is used to calculate the positronium formation, elastic, total, and differential cross-sections. The ionization cross-sections calculated here are obtained employing the complex scattering potentialionization contribution method. To account for the complex molecular structure of the target, an effective potential method is employed in our formalism for the first time. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The same behavior is seen at higher energies, when comparing the results obtained with the SMC method. On the other hand, from the comparison of the present DCSs with the previous calculations for pyridine some similarities are found at scattering angles typically up to 45 deg, whereas at higher angles a significant difference in the angular behavior is found.…”
Section: Resultssupporting
confidence: 73%
“…The same behavior is seen at higher energies, when comparing the results obtained with the SMC method. On the other hand, from the comparison of the present DCSs with the previous calculations for pyridine some similarities are found at scattering angles typically up to 45 deg, whereas at higher angles a significant difference in the angular behavior is found.…”
Section: Resultssupporting
confidence: 73%
“…However, using the SCOP method we have very recently shown that the inclusion of the rotational excitation cross section improves the result in the low-energy region. 38 Hence, we believe that the present method is reliable in the low-energy range as well, giving accurate ionization and electronic excitation cross sections. Ionization Cross Section.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Hence, owing to the lack of reliable data for rotational and vibrational excitation cross sections, the conclusion is incomplete in the low-energy range. However, using the SCOP method we have very recently shown that the inclusion of the rotational excitation cross section improves the result in the low-energy region . Hence, we believe that the present method is reliable in the low-energy range as well, giving accurate ionization and electronic excitation cross sections.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…On the other hand, Antony and coworkers have produced a large quantity of electron scattering data, in particular for those molecules and radicals that are difficult to measure [135,136]. Recent calculations from this group include positron scattering from a variety of atoms and molecules [137,138] and photoionisation cross sections for polyatomic molecules [139,140]. Once these electron/positron/photon collision data are incorporated into IAMDB, it will be integrated into VAMDC.…”
Section: Iamdbmentioning
confidence: 99%